Detection of Escherichia coli in the sewage influent by fluorescent labeled T4 phage - Miyanaga, Kazuhiko; Hijikata, Tomonori; Furukawa, Chiaki; Unno, Hajime; Tanji, Yasunori (Biochemical engineering journal, 2006)
For a precise estimation of sanitary condition, Escherichia coli detection system using E. coli-specific bacteriophage T4 was constructed. To facilitate E. coli detection, T4e − phage which did not produce the lysozyme was constructed and green fluorescent protein (GFP) was displayed on T4e − small outer capside (SOC) protein. This T4e −/GFP can detect E. coli K12 without cell lysis. In this study, we applied T4e −/GFP to the detection of E. coli in the sewage influent. Chromocult ® coliform (CC) agar plates are generally used for simultaneous detection of total coliforms and E. coli. We investigated the number of coliforms and E. coli in the municipal sewage influent by using CC agar plates for 1 year. There were 10 5–10 6 CFU/ml of total coliforms and 10 4–10 5 CFU/ml of E. coli throughout the year. More than 20 strains of E. coli selected from CC agar were infected by T4e −/GFP. The ratio of clear plaque forming E. coli was different every month and very low (annual average 8%). Most of the E. coli showed turbid plaque or no plaque. E. coli formed the turbid plaque showed no-fluorescence, fluorescence only on cell surface due to phage adsorption, or heterogeneous fluorescence among the cells, while E. coli formed clear plaque could be detected because of T4e −/GFP amplification in the cell.